The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/ffj.3192
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of multinuclear microcapsules encapsulating lavender oil by complex coacervation

Abstract: The aim of this work was to encapsulate lavender oil by complex coacervation using gelatin and gum Arabic as encapsulants. The effects of various factors including pH value, the core/wall ratio, wall material concentration, stirring speed, cross‐linkers and homogenization rate on the appearance, mean particle size, yield, loading capacity (LC) and encapsulation efficiency (EE) were investigated. The optimal conditions (pH 3.5, core/wall 3:2, wall material concentration 1%, stirring speed 450 rpm, homogenizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 71 publications
2
71
0
3
Order By: Relevance
“…Xiao et al [34] found that the weight of microcapsules using chitosan as Microcapsules using gelatin and gum arabic as wall materials showed the maximum peak at about 313°C. [40] Hong et al [41] prepared poly(l-lactide) microcapsules for which the weight decreased quickly at 310-410°C. The main weight loss of aromatic nanocapsules was observed at 130-460°C.…”
Section: Thermal Propertiesmentioning
confidence: 98%
“…Xiao et al [34] found that the weight of microcapsules using chitosan as Microcapsules using gelatin and gum arabic as wall materials showed the maximum peak at about 313°C. [40] Hong et al [41] prepared poly(l-lactide) microcapsules for which the weight decreased quickly at 310-410°C. The main weight loss of aromatic nanocapsules was observed at 130-460°C.…”
Section: Thermal Propertiesmentioning
confidence: 98%
“…These problems may be solved by encapsulation technology because a sensitive substance can be entrapped in a membrane or capsule. It can be separated from the deteriorating circumstance (Xiao et al, 2014;Zhu et al, 2016). Encapsulation can also isolate a substance from the surrounding matter reactions (Matsuno & Adachi, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, encapsulation and particularly, nanoencapsulation, is one of the most efficient methods for the formulation of active substances, being a viable and efficient approach to increasing its physical stability and protecting them from interactions with environmental factors, such as, pH, oxygen, light and moisture. [18][19][20] For example, solid lipid microparticles (SLM) were used to encapsulate juniper oil, in order to reduce the volatility of the antimicrobial agent, applied to treatment of acne vulgare. 21 The encapsulation of eugenol and carvacrol into nanometric surfactant micelles for the solubilization in the aqueous phase also resulted in enhanced antimicrobial activity against two pathogenic bacteria.…”
mentioning
confidence: 99%
“…The authors reported one encapsulation efficiency of 66%, the appearance of microcapsules is sphere and the surface is smooth without aggregation. 19 The incorporation of the natural products, in the form of oil eliminates the need for precursor preparation. Balasubramanian et al, utilized the lavender oil fabricated in an electrospun PAN nanofiber for antibacterial and drug delivery applications.…”
mentioning
confidence: 99%